Forms and functions of narration and focalization in some selected poems of Lord Byron : A narratological analysis - Nkamanyang, Pepertua Kininla Lola; Justus Liebig University Giessen (My University, 2008)
In the field of poetry criticism, there are missing concepts that would permit an understanding of how narration and focalization are productive for the analysis of narrative structures in the lyric, and the further function of reproducing issues that are context sensitive. Narratological categories are especially able to provide solutions to this deficit. Furthermore, critics applying the insights of narrative theory to the analysis of Byron s poetry have not adequately explored the diverse representations and functions of narrative elements that are both text-centered and culture specific. Still, the narrative theory of poetry, the significance of which is often narrowed down to a Formalist orientation (the grammar of narrative and text-centered issues) needs to be invigorated with the insights of both Classical and Post-Classical Narratologies to include cultural categories so that they not only take into account the specific type of narrative in poetry but permit the poetry under study to meet its target objectives of reproducing narrative mediation and to an extent specific contexts by narrative means.To break through theoretical and methodological restrictions in the narrative theory of poetry, the study develops an outline of transgeneric narrative theory of poetry criticism, an innovative conceptualization that permits an inclusion of authorial/heterodiegetic narrator, homodiegetic narrator, reflector, perceptual devices, consciousness representation strategies, tense representations and cultural categories (dealing with questions of colonizer, colonized, subjects and subjectivity, such as perspective structure, metannarative forms and communal voice), to enable the a context-sensitive textual analysis of aspects of narrative poems. The role that narrative representations of narration and focalization can play in the analysis of Byron s poetry is shown in the analysis of about twelve novel-length narrative poems written during the Romantic period. In my analysis, poems like Don Juan and "Child Harold s Pilgrimage", traditionally considered as autobiographies, receive a new interpretive perspective deploying linguistic devices, psychonarration strategies, psychoanalogies, extra-representational strategies and narratee signals to discuss a range of possible meanings including the construction of authorial narrative situation. The thesis also deploys the categories of communal voice, linguistic devices and perspective structure to show that ideologies and culture specific contexts like post colonial issues of colonizer, the colonized, subject, subjectivity and power are present in homodiegetic narratives such as "The Prisoner of Chillon". The study also analyzes third-person narrative poems using the categories of free indirect discourse, psychonarration, interior monologue, stream of consciousness technique, internal, external, and collective focalizations to construct heterodiegetic narration, the reflector mode and focalization aiming to highlight the further functions of narration and focalization in reproducing narrators, and psychological characters. By applying narratological categories to the analysis of texts and contexts in Byron s poetry, it is possible to discuss literary genres that are not traditionally viewed as narratives; to link the poetry under study to traditional and modern narrative prose tradition of Joyce and others, and to speak about social contexts especially considering its sociological relevance. By combining results from Structuralist and Post-Classical theory and Cultural history, the study tries to meet not only the need to provide cornerstones for a Transgeneric Narratology which is still in the process of development but also to demonstrate that a Transgeneric narrative theory of poetry can have a theoretical and analytical relevance in the wider context of research in literary and cultural studies. The intellectual relevance of the approach can also be specifically felt in a context like Cameroon where research in Cameroon novels of English expression can benefit from the comprehensive, theoretical and methodological scope of the approach. Needless to say, research in Cameroon is hampered by limited access to both traditional and Post-Classical Interdisciplinary theories.

Im Bereich der Dichtung Kritik, es fehlen Konzepte, wie Erzählung und Fokalization, die für ein Verständnis für die Analyse von narrativen Strukturen in der Lyrik sehr produktive sein könnten, und die kontextsensitive Anwende bringen könnten. Narratologische Kategorien sind vor allem in der Lage, Lösungen für dieses Defizit zu liefern. Darüber hinaus, Kritiker der Erzähltheorie haben noch nicht für die Analyse von Byrons Dichtungen die vielfältigen Darstellungen und Funktionen der narrativen Aspekten ausreichend erforscht, die sowohl Text-zentriert und Kultur spezifisch sind. Dennoch, die narrative Theorie der Dichtung, deren Bedeutung wird oft verengt auf eine formalistische Ausrichtung (die Grammatik der Erzählung und Text-zentrierten Ausgaben) muss mit den Erkenntnissen der klassischen und post-Klassischen Narratologie gestärkt werden, um kulturelle Kategorien umzufassen, so dass sie nicht nur unter Berücksichtigung der spezifischen Art der Erzählung in der Dichtung, sondern erlaubt, die Poesie im Rahmen ihrer Studie Zielvorgaben zu reproduzieren narrative Vermittlung zu treffen und in einem Umfang von spezifischen Kontexten narrativen Mitteln.Um durch theoretische und methodische Einschränkungen in der Erzähltheorie der Dichtung zu brechen, entwickelt die Studie eine Übersicht über transgenerische Erzählttheorie der Dichtung eine innovative Konzeption, die durch Konzepte wie Autor/heterodiegetischen Erzähler, homodiegetic Erzähler, Reflektor, Wahrnehmungs-Geräte, Bewusstseindarstellung eine Strategie ermöglicht. Darstellungen und kulturellen Kategorien (die sich mit Fragen der Kolonialherren, besiedelt, Themen und Subjektivität, wie Perspektive Struktur, metannarative Formen und kommunale Stimme) erlaubt eine kontextsensitive Textanalyse von Aspekten der Erzählung Gedichte. Die Rolle, die narrative Darstellungen von Erzählung und Fokalization in der Analyse der Poesie Byrons spielen kann, wird in der Analyse von etwa zwölf Roman-länge Erzählungen während der Zeit der Romantik geschrieben gezeigt. In der Analyse von "Gedichte wie Don Juan" und "Child Harold´s Pilgrimage", der traditionell als Autobiographien berücksichtigt, erhalten Sie einen neuen Deutungsperspektive Einsatz sprachlicher Mittel, Psychonarration Strategien, Psychoanalogies, Extra-repräsentative Strategien, und Narratee Signale, an eine Reihe von möglichen Bedeutungen diskutieren einschließlich der Errichtung von auktorialen. Die These, setzt auch die Kategorien der kommunalen Stimme, sprachlichen Mittel und Perspektive Struktur zu zeigen, dass Ideologien und kulturspezifischen Kontexten wie postkoloniale Themen von den Kolonisatoren besiedelt, Subjekt, Subjektivität und Macht, in homodiegetic vorliegenden Erzählungen wie "Der Gefangene von Chillon". Die Studie analysiert auch Third-Person-Erzählung Gedichte über die Kategorien der freien indirekten Rede, psychonarration, innerer Monolog, stream of consciousness-Technik, interne, externe und kollektiven focalizations zu heterodiegetic Erzählung zu konstruieren, der Reflektor-Modus und focalization dem Ziel, die weitere Funktionen Highlight des Erzählens und focalization bei der Reproduktion von Erzählern und psychologischen Zeichen. Durch die Anwendung narratologische Kategorien auf die Analyse der Texte und Kontexte, in Byrons Dichtung ist es möglich, den literarischen Gattungen, die traditionell nicht als narratives angesehen zu erörtern; die Poesie unter Studie zur traditionellen und modernen Erzählende Prosa Tradition von Joyce und anderen zu knüpfen und zu sprechen sozialen Kontexten insbesondere angesichts ihrer soziologischen Relevanz. Durch die Kombination der Ergebnisse von Strukturalismus und Post-klassischen Theorie und Kulturgeschichte, versucht die Studie nicht nur die Notwendigkeit, die Eckpfeiler für ein transgenerische Narratologie, die noch im Prozess der Entwicklung, sondern auch zu zeigen, gerecht zu bieten, dass ein transgenerische Erzähltheorie der Dichtung kann eine theoretische und analytische Relevanz in den breiteren Kontext der Forschung in Literatur-und Kulturwissenschaft. Die geistige Bedeutung des Ansatzes können auch speziell in einem Kontext wie Kamerun empfunden werden, die Forschung in Kamerun Romane der englischen Ausdruck aus dem umfangreichen, theoretischen und methodischen Rahmen der Ansatz profitieren können. Unnötig zu sagen, die Forschung in Kamerun wird durch eingeschränkten Zugang zu traditionellen und Post-Klassik behindert interdisziplinäre Theorien.
Forman und Funktionen der Erzählung und Fokalization in ausgewählten Gedichten Lord Byrons : Eine narratologische Analyse
Keywords: Byron; Narratologie; Byron; narratology; ddc:820